The ecology of sandy shores - McLachlan, Anton, 1949-; Brown, A. C. (Alexander Claude), 1931-2005. (Amsterdam ; Boston : Elsevier, 2006)
The definitive volume revised and updated with this new edition.
Front cover; Title page; Copyright page; Acknowledgements; Table of contents; 1: Introduction; 2: The Physical Environment; 3: The Interstitial Environment; 4: Beach and Surf-zone Flora; 5: Sandy-beach Invertebrates; 6: Adaptations to Sandy-beach Life; 7: Benthic Macrofauna Communities; 8: Benthic Macrofauna Populations; 9: Interstitial Ecology; 10: Surf-zone Fauna; 11: Turtles and Terrestrial Vertebrates; 12: Energetics and Nutrient Cycling; 13: Coastal Dune Ecosystems and Dune/Beach Interactions; 14: Human Impacts; 15: Coastal Zone Management; 16: Glossary; 17: References; 18: Appendices.
Revised edition of: Ecology of sandy shores / A.C. Brown & A. McLachlan.
Includes bibliographical references (pages 329-351) and index.
Description based on online resource, title from digital title page (viewed on September 17, 2024)
eBooks on EBSCOhost
Keywords: Seashore ecology; Sand dune ecology; Beaches; Bathing beaches; Écologie des rivages; Écologie des dunes; Plages; bathing beaches; beaches; NATURE -- Ecosystems & Habitats -- Coastal Regions & Shorelines; Bathing beaches; Beaches; Sand dune ecology; Seashore ecology; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.